PENGARUH PENGGUNAAN MASKER GEL DAUN JAMBU BIJI TERHADAP PERAWATAN KULIT WAJAH BERJERAWAT - Bahri, Idria; Hayatunnufus (Universitas Negeri Surabaya, 2023)
Guava leaves have antibacterial activity against propionibacterium acnes, staphylococcus aureus and staphylococcus epidermidis. The flavonoid content which functions as an antioxidant and antibacterial and Vitamin C which functions to protect the skin from free radicals make guava leaves have the potential to treat acne. This study aims to analyze the effect of using a guava leaf gel mask on facial skin care for acne. This research uses a quasi-experimental method with a non-equivalent control group design. Using a research sample of 9 people using purposive sampling technique. The type of data used is primary data. Data analysis was carried out using the ANOVA test and continued with the Duncan test. The results of the study showed that there were differences in the effect of acne facial skin care between the three treatment groups which showed significant results on each indicator of acne color with Fcount (5.744)>Ftable (3.072), the shape of the acne was Fcount (6.291)>Ftable (3.072), volume acne obtained Fcount (7.989)>Ftable (3.072), and the number of acne obtained Fcount (7.989)>Ftable (3.072) for the level of facial skin care for acne. Each indicator followed by the Duncan test shows significant group differences, because Fcount is greater than Ftable. Regular use of the guava leaf gel mask with a frequency of 1x7 days gives quite significant results for the better. Keywords: effect; guava leaf gel mask; acne facial skin care.